Introduction [in Food and Agriculture in Ethiopia] - Dorosh, Paul A.; Rashid, Shahidur (University of Pennsylvania Press, 2012)
Indeed, the reality of Ethiopia’s agriculture and food security situation is complex because of variations across space within Ethiopia as well as variations over time due to changes in policies, weather shocks, and other factors. A complete picture of Ethiopia’s agriculture and food security must include both the very serious acute and chronic food insecurity problems faced by many Ethiopians and the progress achieved in other areas and at the national level.